2004
DOI: 10.1074/jbc.m311020200
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1 Is a Transplasma Membrane NADH-Ferricyanide Reductase

Abstract: Porin isoform 1 or VDAC (voltage-dependent anionselective channel) 1 is the predominant protein in the outer mitochondrial membrane. We demonstrated previously that a plasma membrane NADH-ferricyanide reductase activity becomes up-regulated upon mitochondrial perturbation, and therefore suggested that it functions as a cellular redox sensor. VDAC1 is known to be expressed in the plasma membrane; however, its function there remained a mystery. Here we show that VDAC1, when expressed in the plasma membrane, func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
143
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 57 publications
4
143
0
Order By: Relevance
“…27 This finding together with the current demonstration of the appearance of VDAC electrophysiological activity in apoptotic cells suggests a dual role for the plasma membrane VDAC1 protein, that is, maintenance of cellular redox homeostasis in normal cells and cell volume regulation in apoptotic cells. To further investigate this hypothesis, we measured NADH (-ferricyanide) reductase activity in intact control and STS-treated HT22 cells.…”
Section: Vdac In the Plasma Membranementioning
confidence: 61%
See 1 more Smart Citation
“…27 This finding together with the current demonstration of the appearance of VDAC electrophysiological activity in apoptotic cells suggests a dual role for the plasma membrane VDAC1 protein, that is, maintenance of cellular redox homeostasis in normal cells and cell volume regulation in apoptotic cells. To further investigate this hypothesis, we measured NADH (-ferricyanide) reductase activity in intact control and STS-treated HT22 cells.…”
Section: Vdac In the Plasma Membranementioning
confidence: 61%
“…25 However, several reports, using different techniques, have shown VDAC-like channels in the plasma membrane of multiple cell types, including neurons. [14][15][16][26][27][28] A major argument against the presence of functional VDACs in the plasma membrane has been that this would result in increased membrane permeability that would not be compatible with cell survival. Therefore, as suggested by Yu and Forte, 25 it is likely that these channels are not functional under normal conditions.…”
Section: Vdac In the Plasma Membranementioning
confidence: 99%
“…Indeed, VDAC is mainly known as a voltage-gated OM pore, allowing the diffusion of solutes o5 kDa (Colombini, 1983;Zizi et al, 1998). However, other functions such as apoptosis regulation via an interaction with Bcl-2 family members (Shimizu et al, 1999;Vander Heiden et al, 2000;Cheng et al, 2003;Rostovtseva et al, 2004;Zaid et al, 2005), kinase binding (Azoulay-Zohar et al, 2004), NADH ferricyanide reductase activity (Baker et al, 2004) as well as calcium transport (Gincel et al, 2001) have been reported. Thus, preliminarily, we observed that GAPDH increases the Ca 2 ĂŸ uptake through VDAC into proteoliposomes and not into plain liposomes (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the lack of correlation between VDAC protein expression and maxi-anion channel activity strongly argued against the long held hypothesis of plasmalemmal VDAC being maxi-anion channel, but indicate that none of the three individual isoforms of VDAC can be responsible for the maxi-anion channel. The plasmalemmal VDAC proteins may perform some other functions, such as being a receptor for plasminogen kringle 5 [171] or a trans-plasma membrane NADH-ferricyanide reductase [172], activities that are unrelated to the maxianion channel activity.…”
Section: Puzzle Of the Molecular Identity Of The Maxi-anion Channelmentioning
confidence: 99%